2005
DOI: 10.1007/s00018-004-4464-6
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 chaperones: Cellular functions and molecular mechanism

Abstract: Abstract. Hsp70 proteins are central components of the cellular network of molecular chaperones and folding catalysts. They assist a large variety of protein folding processes in the cell by transient association of their substrate binding domain with short hydrophobic peptide segments within their substrate proteins. The substrate binding and release cycle is driven by the switching of Hsp70 between the low-affinity ATP bound state and the high-affinity ADP bound state. Thus, ATP binding andCMLS, Cell. Mol. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
2,143
3
27

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,499 publications
(2,211 citation statements)
references
References 123 publications
38
2,143
3
27
Order By: Relevance
“…[55] These proteins function as general molecular chaperones that maintain or return proteins to their functional state, minimize aggregation of proteins in their non-native conformation, and target unfolded or aggregated proteins for degradation or removal [56]. HSP70  has vital housekeeping functions, maintaining homeostasis and protecting cells against thermal and oxidative stress [57] and was up-regulated in Culex larvae whether they had been infected with blastospores or conidia suggesting that HSP70 played a key role in stress management in mosquito larvae. Castillo et al [58] found that up-regulation of HSP genes is evidence of increasing stress in response to pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…[55] These proteins function as general molecular chaperones that maintain or return proteins to their functional state, minimize aggregation of proteins in their non-native conformation, and target unfolded or aggregated proteins for degradation or removal [56]. HSP70  has vital housekeeping functions, maintaining homeostasis and protecting cells against thermal and oxidative stress [57] and was up-regulated in Culex larvae whether they had been infected with blastospores or conidia suggesting that HSP70 played a key role in stress management in mosquito larvae. Castillo et al [58] found that up-regulation of HSP genes is evidence of increasing stress in response to pathogen infection.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70s/DnaKs are composed of a highly homologous N-terminal ATPase domain, a substrate-binding domain and a C-terminal variable domain [5]. The molecular chaperone function of Hsp70/DnaK proteins seems to be based on its ATPase activity and this activity is stimulated by Hsp40/ DnaJ, GrpE and substrate binding [6].…”
Section: Introductionmentioning
confidence: 99%
“…At least five proteins have been shown to be monoubiquitylated by Parkin. Two of these substrates are protein chaperones of the heat‐shock protein (Hsp) 70 family—Hsp70 and Hsc70—that facilitate the folding of newly synthesized proteins as well as the refolding of misfolded and aggregated proteins (Mayer & Bukau 2005; Moore et al . 2008).…”
Section: Regulation Of Neuronal Proteins By Monoubiquitylationmentioning
confidence: 99%